共同希望语言学院2019届学生HSK5级阅读猜词应对策略调查分析 - Hui Yi, Wong; Lho, Lysa (Journal of Maobi, 2024)
The HSK (Hanyu Shuiping Kaoshi) is an important benchmark for assessing one's proficiency in Chinese among Chinese learners. As the exam levels increase, so does the number of vocabulary words required to be mastered. Learners are inevitably influenced to some extent by their own understanding of vocabulary when engaging in HSK reading comprehension. The author suggests that guessing strategies can help students mitigate this influence, providing an additional approach for dealing with unfamiliar words during comprehension. This study focuses on the 2019 graduates of the Hope Language Institute, using a combination of questionnaire surveys, tests, and interviews to collect data, followed by analysis using inductive methods. The aim of this research is to assist students in their reading comprehension while also raising awareness of the importance of employing and researching guessing strategies in reading. According to the survey results, the two most commonly used strategies by the 2019 graduates during reading are skimming and guessing strategies. Among the guessing strategies commonly used are morpheme-based guessing, context-based guessing, and character-based guessing. Additionally, common problems encountered by students in the guessing process include low recognition of semantic radicals, confusion over polysemous morphemes, and insufficient vocabulary.